Where and How Do Aging Processes Take Place in Everyday Life? Answers From a New Materialist Perspective - Höppner, Grit; Urban, Monika (Frontiers in Sociology, 2018)
In the last decade, the focus of studies on age and aging has fundamentally changed from biological to symbolic, discursive, and cultural phenomena. Currently, the most studied topic in material gerontology is the materiality of age and aging in the context of everyday life. Scholars in this area have thus been making an important contribution to a material understanding of aging processes. As we understand them, however, both social constructivist and material gerontological concepts reach their limit when it comes to the questions of where and how aging processes actually take place in everyday life. In order to answer these two questions, we review social constructivist ideas with a particular focus on the ‘doing age’ concept and material gerontological assumptions regarding human subjects, their material environments, and their relations. We then suggest rethinking bodily limitations and agencies addressed by scholars in the field of new materialism. The aim is to develop a new materialist-inspired understanding of aging processes that helps to reconstruct the material-discursive co-production of aging processes. These processes are deployed as mutual entanglements of materiality and meaning as well as of humans and non-human agency. This approach emphasizes the decentralization of the human actor and thus helps to map the material-discursive complexity of aging processes as relational co-products of humans and non-humans in everyday life.